Back Matter Vol. 55, No. 3 September (2019) - Matter, Back (Folia Medica Indonesiana, 2019)
Plague disease remains a public health problem in the world. According to the International Health Regulations (IHR), an outbreak is an infectious disease that has the potential to cause an outbreak. The purpose of this study was to analyze a significant relationship between human behavior and the environment with the density of the number of rats in the focus, threatened and outbreak-safe areas in Tutur Regency, Pasuruan Regency, in 2016. This was an observational analytic study with cross correlation sectional where the research variables are population behavior, environment, and the number of rat densities observed once at a time. The results showed that there was no significant relationship between the behavior (knowledge, attitude, and practice) of the population with the density of rats in the focus area of the Surorowo hamlet outbreak, in the endangered outbreaks of the Ngaro hamlet, and in the outbreak-safe area of the North Ngandong hamlet in Tutur District. Whereas, there is a significant relationship between environmental conditions and the amount of rat density in the focus area of the outbreak of the Surorowo hamlet (p: 0.047 or p <0.05), the threatened area of the Ngaro hamlet (p: 0.036 or p <0.05), and at outbreak-safe areas in Andong Utara hamlet (p: 0.047 or p <0.05). Conclusion: Environmental conditions are associated with the amount of rat density either in the outbreak, in focus, threatened, or in safe areas. That it is necessary to control environmental risk factors to reduce the amount of rat density.